The Influence Of Lambe Turah's Account Postings On The Driving Of Netizens' Opinions - Fadhilah Nur Rohmah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
The emergence of social media platforms has revolutionized the way information is disseminated and opinions are formed. Lambe Turah, an influential anonymous social media account, has gained considerable attention for its provocative and controversial postings. This study aims to investigate the influence of Lambe Turah's account postings on the driving of netizens' opinions. To achieve this objective, a mixed-methods approach was employed, combining qualitative content analysis and surveys. First, a systematic analysis of Lambe Turah's posts and interactions was conducted to identify the prevalent themes, sentiments, and techniques employed. The analysis was followed by surveys administered to a diverse sample of netizens to assess their exposure to Lambe Turah's posts and the subsequent impact on their opinions. Preliminary findings suggest that Lambe Turah's account postings have a significant influence on shaping netizens' opinions. The account's ability to generate attention, controversy, and engagement plays a vital role in drawing users' attention to particular issues and framing public discourse. Moreover, the anonymous nature of Lambe Turah enables it to disseminate information without being directly accountable, potentially impacting the credibility and verifiability of the shared content. However, the study also acknowledges the potential risks associated with Lambe Turah's influence. The spread of misinformation, polarization, and the amplification of hate speech are observed as potential negative outcomes resulting from the account's postings. These findings emphasize the importance of critical thinking, media literacy, and responsible consumption of social media content to mitigate the potentially detrimental effects of anonymous accounts like Lambe Turah.